Electrochemical polymerization of o-anisidine on low carbon steel from aqueous salicylate solution: corrosion protection study - Wankhede, M. G.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
The electrochemical polymerization of o-anisidine was carried out on low carbon steel from an aqueous salicylate medium using cyclic voltammetry. The resulting poly(o-anisidine) coatings were uniform and adherent to the steel substrates. These coatings were characterized by cyclic voltammetry, LTV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction measurements and scanning electron microscopy. The ability of the poly(o-anisidine) coatings to protect low carbon steel in an aqueous 3% NaCl was evaluated by the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(o-anisidine) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; low carbon steel; poly(o-anisidine) coatings

Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Formation of poly(o-anisidine) coatings on copper from aqueous salicylate solution - Chaudhari, Sudeshna; Mandale, A. B.; Patil, K. R.; Sainkar, S. R.; Patil, P. P. (Surface & Coatings Technology, 2006)
Poly(o-anisidine) coatings have been electrosynthesized by using cyclic voltammetry on copper from an aqueous salicylate medium. Cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and X-ray photoelectron spectroscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-anisidine on copper substrate. Cyclic voltammetry accompanied by the X-ray photoelectron spectroscopy was used to characterize the surface modifications induced by polarizing the copper substrate in the aqueous salicylate solution (without monomer). It was shown that the polarization of the copper in the aqueous salicylate medium results into the passivation of its surface via the formation of Cu(2)O and/or copper salicylate complex. It was found that the electrochemical polymerization of o-anisidine takes place after the passivation of the copper substrate via fort-nation of Cu(2)O and/or copper salicylate complex and results into the formation of shiny, uniform and strongly adherent poly(o-anisidine). The optical absorption spectroscopy reveals the formation of emraldine salt form of poly(o-anisidine). This study offers an electrochemical polymerization recipe to synthesize strongly adherent poly(o-anisidine) coating on copper from aqueous media for possible use in corrosion protection application. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; corrosion protective coatings; cyclic voltammetry; poly(o-anisidine) coatings